Determination of High School Teacher Performance: The Role of Workload - Ilyas Ilyas; Herliyus Efendi (Global Sustainability Research Institute, 2024)
Introduction: This study aims to investigate the influence of intellectual intelligence and emotional intelligence on the performance of high school teachers, by considering the moderating role of workload. Methods: This research uses 95 surveys as the data collection method. The analytical method in this research is multiple linear regression and moderation analysis, then testing the research instrument using product moment for validity testing and Cronbach alpha for reliability testing, while testing classical assumptions using normality, multicollinearity, and heteroscedasticity tests. Results: The results of this research show that intellectual intelligence and emotional intelligence have a positive effect on performance, this indicates that the presence of both intellectual and emotional intelligence will increase the quality of work of high school teachers. Furthermore, the workload does not moderate the relationship between intellectual and emotional intelligence on the performance of high school teachers. Conclusion and suggestion: The implications of these findings can be used as a basis for developing more effective training and workload management programs to improve the performance of high school teachers.